Landasan dan Dampak Hukum Test Wawasan Kebangsaan KPK: Suatu Kajian Doktrinal - Simamora, Anggiat P.; Nababan, Ramsul (Universitas Medan Area, 2021)
The National Insight Test which was followed by KPK employees in the context of changing their status to ASN has given rise to pros and cons. The results of the TWK which later gave birth to SK 652, the KPK is considered by some to have no legal basis or is considered to have committed human rights violations. This paper analyzes the problem from the legal aspect. The questions that will be answered in this paper are: 1). Does TWK have a juridical basis; 2). What is the legal impact of TWK on KPK employees; 3). What efforts should be made by KPK employees who do not meet the requirements in fighting for their rights to become ASN. The research is a doctrinal research that uses a statutory and conceptual approach. From the results of the study it was found that TWK is a requirement made by the KPK leadership in order to transfer the status of KPK employees to ASN. The authority of the KPK in making these conditions comes from PP41/2020. The legal impact of TWK is the transition of the status of KPK employees who meet the requirements to become ASN. While the legal impact for those who do not meet the requirements is the loss of their rights to become ASN and ASN candidates starting 2 years after the enactment of Law 19/2019